2006
DOI: 10.1108/17410390610658478
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management practices of SMEs: from a business growth perspective

Abstract: Purpose -The purpose of this research is to show that small or medium enterprises (SMEs) have significant impacts on supply chain performance. They may take the roles of suppliers, producers, distributors, and customers. In this paper large firms and SMEs are compared in terms of strategic and operational choices. Design/methodology/approach -SMEs are classified on two dimensions -chain relationship position and strategic focus. Four types of SME characteristics are discussed: efficiency, coordination, collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 21 publications
(38 reference statements)
0
104
0
9
Order By: Relevance
“…Indeed, most of the SMEs have only few major or stronger customers who have more demands (John Morrisey & Pittaway, 2006). Therefore, SMEs develop more closer, personal and long term relationships with their customers (Bhutta et al 2007;Hong & Jeong, 2006). Min and Mentzer (2004) suggested that close and good customer relationship is essential for understanding and fulfilling their needs.…”
Section: Customer Relationshipmentioning
confidence: 99%
“…Indeed, most of the SMEs have only few major or stronger customers who have more demands (John Morrisey & Pittaway, 2006). Therefore, SMEs develop more closer, personal and long term relationships with their customers (Bhutta et al 2007;Hong & Jeong, 2006). Min and Mentzer (2004) suggested that close and good customer relationship is essential for understanding and fulfilling their needs.…”
Section: Customer Relationshipmentioning
confidence: 99%
“…Hong and Jeong ( 2006), defines SCM as a set of approaches utilized to effectively integrate suppliers, manufacturers, logistics, and customers for improving the long-term performance of individual companies and supply chain as a whole. SCM can also be defined as an actor-oriented approach focusing on how to organize and manage the flow of materials from "point of origin" to "end-user" as the point of departure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Study has also indicated that managers may not quickly comprehend the appropriateness and applicability of benchmarking data in their organization due to incompatible factors involved in benchmarking such as size, location, structure, age, number of employees, sales volume and ownership. The managers' roles are beyond the exercise but also include growing dynamic changes that could transform SMEs from being efficient towards innovation [13]. Singh [14] also posited that the leadership in a company could determine the success rate of the exercise in the business.…”
Section: Literature Reviewmentioning
confidence: 99%